Synthesis of Sulphoaluminate-Belite Clinkers (Texas Journal of Agriculture and Biological Sciences, 2023)
By firing at a temperature of 1523…1673 K, sulfoaluminate-belite clinkers were obtained containing 10…60% calcium sulfoaluminate, 40…90% dicalcium silicate and 10…30% excess calcium sulfate. The analysis of these clinkers and their electron microscopic examination testify to the formation of these minerals during the firing process.